Search 83,509 tutors
FIND TUTORS
Ask a question
0 0

3x^2-12y^2+6x+48y-93=0

Tutors, please sign in to answer this question.

1 Answer

This is equation of hyperbola in general form which you need to change it to standard form to see the information asked. You need to complete the square for both x and y.
 
3(x^2+2x) - 12(y^2-4y) = 93
3(x^2+2x+1) - 12(y^2-4y+4) = 93 + 3 -48
3(x+1)^2 - 12(y-2)^2 = 48
 
divide both side by 48
 
(x+1)^2/16 - (y-2)^2/4 = 1
 
now center is at (-1, 2)
vertices (-5,2) and (3,2)
Slopes of the asymptotes - 1/2 and 1/2